UJI AKTIVITAS ANTIBAKTERI EKSTRAK BUAH TOMAT (Solanum lycopersicum L.) TERHADAP BAKTERI Propionibacterium acnes - Elly Purwati (AFAMEDIS, 2021)
Acne is a skin infection disease, one of which is caused by bacteria. Treatment with antibiotics can cause resistance, so it is needed alternative treatment of natural ingredients and tomatoes (Solanum lycopersicum L.) is one of the natural ingredients that contain alkaloid compounds, flavonoids, saponins and tannins that are known to have an antibacterial effect. The purpose of this study was to find out the antibacterial activity of tomato extract against the growth of Propionibacterium acnes bacteria. Tomato fruit extract is divided into 3 concentration series (20%, 40% and 60%). Testing the taste of Propionibacterium acnes using diffusion method (Kirby and Bauer diffusion) by disc diffusion. Clindamycin is used as a positive control, and Aquadest as a negative control. The results of the study showed that the concentration of inhibition zone was 20% with an average of 1.08 mm, a concentration of 40% with an average of 3.74 mm, a concentration of 60% with an average of 5.14 mm, and clindamycin (positive control) with an averageof 9.15 mm and test data Kruskall-wallis obtained a value of 0.00 less than 0.05, it can be concluded that tomato fruit extract (Solanum lycopersicum L.) can inhibit the growth of Propionibacterium acnes bacteria with a significant difference andit is known that tomato fruit extract (Solanum lycopersicum L.) concentration of 60 % the most influential in inhibiting the growth of Propionibacterium acnes bacteria. Keywords : Acne, Tomato (Solanum lycopersicum L.), Propionibacterium acnes, Antibacteria